Второе число - х Первое - 5/12 х Третье - 35/72 х Среднее арифметическое: (5/12 х + х + 35/72 х ) : 3 = 274 /225 30/72 х + х + 35/72 х = 274/225 * 3/1 1 65/72 х = 274/75 х= 274/75 : 1 65/72 = 274/75 * 72/137= (2*24)/ (25*1) =48/25 х= 1 23/25 - второе число 5/12 * 48/25 = (1*4)/(1*5)=4/5 - первое число 35/72 * 48/25 = ( 7*2) / (3*5) = 14/15 - третье число
=8
=87a + 5b = 8a
=87a + 5b = 8a5b = 8a - 7a
=87a + 5b = 8a5b = 8a - 7aa = 5b
=87a + 5b = 8a5b = 8a - 7aa = 5b\frac{5a+7b}{b}= \frac{5*5b+7b}{b} = \frac{25b+7b}{b}= \frac{32b}{b} =32
=87a + 5b = 8a5b = 8a - 7aa = 5b\frac{5a+7b}{b}= \frac{5*5b+7b}{b} = \frac{25b+7b}{b}= \frac{32b}{b} =32 b
=87a + 5b = 8a5b = 8a - 7aa = 5b\frac{5a+7b}{b}= \frac{5*5b+7b}{b} = \frac{25b+7b}{b}= \frac{32b}{b} =32 b5a+7b
=87a + 5b = 8a5b = 8a - 7aa = 5b\frac{5a+7b}{b}= \frac{5*5b+7b}{b} = \frac{25b+7b}{b}= \frac{32b}{b} =32 b5a+7b
=87a + 5b = 8a5b = 8a - 7aa = 5b\frac{5a+7b}{b}= \frac{5*5b+7b}{b} = \frac{25b+7b}{b}= \frac{32b}{b} =32 b5a+7b =
=87a + 5b = 8a5b = 8a - 7aa = 5b\frac{5a+7b}{b}= \frac{5*5b+7b}{b} = \frac{25b+7b}{b}= \frac{32b}{b} =32 b5a+7b = b
=87a + 5b = 8a5b = 8a - 7aa = 5b\frac{5a+7b}{b}= \frac{5*5b+7b}{b} = \frac{25b+7b}{b}= \frac{32b}{b} =32 b5a+7b = b5∗5b+7b
=87a + 5b = 8a5b = 8a - 7aa = 5b\frac{5a+7b}{b}= \frac{5*5b+7b}{b} = \frac{25b+7b}{b}= \frac{32b}{b} =32 b5a+7b = b5∗5b+7b
=87a + 5b = 8a5b = 8a - 7aa = 5b\frac{5a+7b}{b}= \frac{5*5b+7b}{b} = \frac{25b+7b}{b}= \frac{32b}{b} =32 b5a+7b = b5∗5b+7b =
=87a + 5b = 8a5b = 8a - 7aa = 5b\frac{5a+7b}{b}= \frac{5*5b+7b}{b} = \frac{25b+7b}{b}= \frac{32b}{b} =32 b5a+7b = b5∗5b+7b = b
=87a + 5b = 8a5b = 8a - 7aa = 5b\frac{5a+7b}{b}= \frac{5*5b+7b}{b} = \frac{25b+7b}{b}= \frac{32b}{b} =32 b5a+7b = b5∗5b+7b = b25b+7b
=87a + 5b = 8a5b = 8a - 7aa = 5b\frac{5a+7b}{b}= \frac{5*5b+7b}{b} = \frac{25b+7b}{b}= \frac{32b}{b} =32 b5a+7b = b5∗5b+7b = b25b+7b
=87a + 5b = 8a5b = 8a - 7aa = 5b\frac{5a+7b}{b}= \frac{5*5b+7b}{b} = \frac{25b+7b}{b}= \frac{32b}{b} =32 b5a+7b = b5∗5b+7b = b25b+7b =
=87a + 5b = 8a5b = 8a - 7aa = 5b\frac{5a+7b}{b}= \frac{5*5b+7b}{b} = \frac{25b+7b}{b}= \frac{32b}{b} =32 b5a+7b = b5∗5b+7b = b25b+7b = b
=87a + 5b = 8a5b = 8a - 7aa = 5b\frac{5a+7b}{b}= \frac{5*5b+7b}{b} = \frac{25b+7b}{b}= \frac{32b}{b} =32 b5a+7b = b5∗5b+7b = b25b+7b = b32b
=87a + 5b = 8a5b = 8a - 7aa = 5b\frac{5a+7b}{b}= \frac{5*5b+7b}{b} = \frac{25b+7b}{b}= \frac{32b}{b} =32 b5a+7b = b5∗5b+7b = b25b+7b = b32b
=87a + 5b = 8a5b = 8a - 7aa = 5b\frac{5a+7b}{b}= \frac{5*5b+7b}{b} = \frac{25b+7b}{b}= \frac{32b}{b} =32 b5a+7b = b5∗5b+7b = b25b+7b = b32b =32